2023
DOI: 10.1002/jimd.12646
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of GM1 gangliosidosis—Retrospective cohort study of 61 French patients from 1998 to 2019

Abstract: GM1 gangliosidosis is a rare lysosomal storage disorder associated with β‐galactosidase enzyme deficiency. There are three types of GM1 gangliosidosis based on age of symptom onset, which correlate with disease severity. In 2019, we performed a retrospective multicentric study including all patients diagnosed with GM1 gangliosidosis in France since 1998. We had access to data for 61 of the 88 patients diagnosed between 1998 and 2019. There were 41 patients with type 1 (symptom onset ≤6 months), 11 with type 2a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Higaki et al [ 30 ] showed the screening results for new chaperones to treat GM1-gangliosidosis, an LSD caused by a deficiency of the β-galactosidase enzyme [ 31 ]. Concurrently with the design of new chaperones for the enzyme, they described its response to approved molecules.…”
Section: Shooting At Random: the Valuable Results Of High-throughput ...mentioning
confidence: 99%
“…Higaki et al [ 30 ] showed the screening results for new chaperones to treat GM1-gangliosidosis, an LSD caused by a deficiency of the β-galactosidase enzyme [ 31 ]. Concurrently with the design of new chaperones for the enzyme, they described its response to approved molecules.…”
Section: Shooting At Random: the Valuable Results Of High-throughput ...mentioning
confidence: 99%